Crosslinked Carbon Nanotube Aerogel Films Decorated with Cobalt Oxides for Flexible Rechargeable Zn–Air Batteries. Issue 29 (8th June 2017) - Zeng, Sha; Chen, Hongyuan; Wang, Han; Tong, Xiao; Chen, Minghai; Di, Jiangtao; Li, Qingwen
Abstract : Air electrodes with high catalytic activity are of great importance for rechargeable zinc–air batteries. Herein, a flexible, binder‐free composite air electrode for zinc–air batteries is reported, which utilizes a lightweight, conductive, and crosslinked aerogel film of carbon nanotubes (CNTs) functioned as a 3D catalyst‐supporting scaffold for bifunctional cobalt (II/III) oxides and as a current collector. The composite electrode shows high catalytic activities for both oxygen reduction reaction and oxygen evolution reaction, resulting from the synergistic effect of nitrogen‐doped CNTs and spinel Co3 O4 nanoparticles. Solid‐state Zn–air batteries assembled using such free‐standing air electrodes (without the need of additional current collectors) are bendable and show low resistances, low charge/discharge overpotentials, and a high cyclic stability. Abstract : Crosslinked, ultralightweight carbon nanotubes aerogel films fabricated by chemical vapor deposition are utilized as conductive scaffolds for supporting cobalt oxide nanoparticles, resulting in composite catalysts with high‐performance synergistic catalytic activities for oxygen reduction reaction and oxygen evolution reaction. Zn–air batteries assembled using such composite catalysts are bendable and show low resistances, low overpotentials, and a high cyclic stability.